2012
DOI: 10.1016/j.ocecoaman.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ecological, economic and social aspects to generate useful management information under the EU Directives' ‘ecosystem approach’

Abstract: Integrating ecological, economic and social aspects to generate useful management information under the EU Directives' 'Ecosystem Approach'  Ecological and economic information should be integrated at the habitat level  System valuation is only possible when a holistic approach is applied  The DPSIR (driver, pressure, state, impact, response) framework is a helpful technical tool here  Future application and further development of (Ecological) Network Analysis techniques for management purposes is strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 111 publications
1
93
0
1
Order By: Relevance
“…New Zealand conifers are generally regarded as being tolerant of poor soils (Coomes and Bellingham, 2011;de Jonge et al, 2012), and have an affinity for leached, low nutrient, acid or poorly drained soils that form in ever-wet environments and some (Dacrydium cupressinum, Dacrycarpus dacrydioides, Lepidothamnus intermedius, Manoao colensoi, Libocedrus plumosa, Halocarpus bidwillii, H. biformis) are characteristic of such sites (Richardson et al, 2005b). Where the climate supports tall trees, conifers usually dominate the tree biomass as there are only three tall angiosperm trees that tolerate wetlands (Elaeocarpus hookerianus, Laurelia novaezelandiae and Syzygium maire; McGlone, 2009).…”
Section: A Glacial-interglacial Perspective On the Environmental Nichmentioning
confidence: 99%
See 1 more Smart Citation
“…New Zealand conifers are generally regarded as being tolerant of poor soils (Coomes and Bellingham, 2011;de Jonge et al, 2012), and have an affinity for leached, low nutrient, acid or poorly drained soils that form in ever-wet environments and some (Dacrydium cupressinum, Dacrycarpus dacrydioides, Lepidothamnus intermedius, Manoao colensoi, Libocedrus plumosa, Halocarpus bidwillii, H. biformis) are characteristic of such sites (Richardson et al, 2005b). Where the climate supports tall trees, conifers usually dominate the tree biomass as there are only three tall angiosperm trees that tolerate wetlands (Elaeocarpus hookerianus, Laurelia novaezelandiae and Syzygium maire; McGlone, 2009).…”
Section: A Glacial-interglacial Perspective On the Environmental Nichmentioning
confidence: 99%
“…Pollen diagrams confirm this and peat sites usually show conifer sequences with Dacrycarpus dacrydiodes at the fertile, often swamp or lagoon beginning of the sequence, and Dacrydium cupressinum, Manaoa colensoi, Lepidothamnus intermedius, and Halocarpus bidwillii at the infertile bog later stages (McGlone, 2009). However, in some situations conifers are quick to colonize fertile soils after disturbance, losing ground to angiosperm broadleaves as the succession proceeds, and this is most apparent in the pollen record after large-scale volcanic disturbance (Wilmshurst and McGlone, 1996;Horrocks and Ogden, 1998) but it also occurs after smaller scale disturbances (Bray, 1989;Carswell et al, 2007;de Jonge et al, 2012).…”
Section: A Glacial-interglacial Perspective On the Environmental Nichmentioning
confidence: 99%
“…and ecological importance. Recently, various contributions (e.g., Chernetsky et al 2010;de Jonge et al 2012; have indicated that tidal characteristics can change significantly due to anthropogenic measures. These changes can endanger safety, i.e., changes in the surface elevation may cause flooding in the surrounding area, and transport (related to the changes in the three-dimensional velocity field) or accumulation of sediments and pollutants which leads to poor quality of water.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable development is a complex issue, involving strongly interconnected ecological, social, and economic aspects of an ecosystem, now and in the future (de Jonge et al 2012). In fact, according to Kiker et al (2005), 'Decision-making in environmental projects can be complex and seemingly intractable, principally because of the inherent trade-offs between socio-political, environmental, ecological, and economic factors'.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-criteria analyses (MCA) have been recommended as useful tools to ensure an integrated management of an ecosystem, allowing the incorporation of different sets of data (e.g., Villa et al 2002;Pavlikakis and Tsihrintzis 2003;de Jonge et al 2012). MCA is a stepwise process that allows the comparing of decision alternatives with multiple and often complex impacts (Hermann et al 2007).…”
Section: Introductionmentioning
confidence: 99%